Battery‐supercapacitor hybrid energy storage system in standalone DC microgrids: areview. Issue 4 (31st January 2017) - Jing, Wenlong; Hung Lai, Chean; Wong, Shung Hui Wallace; Wong, Mou Ling Dennis
Abstract : Global energy challenges have driven the adoption of renewable energy sources. Usually, an intelligent energy and battery management system is deployed to harness the renewable energy sources efficiently, whilst maintaining the reliability and robustness of the power system. In recent years, the battery‐supercapacitor based hybrid energy storage system (HESS) has been proposed to mitigate the impact of dynamic power exchanges on battery's lifespan. This study reviews and discusses the technological advancements and developments of battery‐supercapacitor based HESS in standalone micro‐grid system. The system topology and the energy management and control strategies are compared. The study also discusses the technical complexity and economic sustainability of a standalone micro‐grid system. A case study of a standalone photovoltaic‐based micro‐grid with HESS is presented.